Modification of malachite green by Fomes sclerodermeus and reduction of toxicity to Phanerochaete chrysosporium - Papinutti, V.L. (2004)
Malachite green (MG) is a triphenylmethane dye used as a fungicide but also possesses a high toxicity to mammalian cells. The toxicity of MG to Fomes sclerodermeus and Phanerochaete chrysosporium was assessed. P. chrysosporium was highly sensitive to the dye and it was unable to grow on solid media containing 64 μM of MG, lower concentrations caused a delay in growth. The radial growth of F. sclerodermeus was not affected at this concentration and up to 128 μM. In liquid media both fungi were more sensitive. F. sclerodermeus not only was able to grow in the presence of high concentrations of MG, but also it was able to decolorize and detoxify the dye. MG treated with supernatants containing high laccase activity in the presence or absence of 1-hydroxybenzotriazole (1-HBT) gave a colorless product (DMG) that was not toxic to P. chrysosporium and other white rot fungi tested. On the basis of the data of maximal absorbance, it is probable that the mechanism involved in the modification of the dye was different if 1-HBT was added to the reaction. © 2004 Federation of European Microbiological Societies. Published by Elsevier B.V. All rights reserved.